Toxicology of carbon nanomaterials in the Caenorhabditis elegans model: current status, characterization, and perspectives for testing harmonization - Côa, Francine; Bortolozzo, Leandro de Sá; Ávila, Daiana Silva; Souza Filho, Antonio G.; Martinez, Diego Stéfani Teodoro (Frontiers in Carbon, 2023)
Carbon nanomaterials are promising advanced materials for novel technologies. Biosafety studies are therefore mandatory to support their safe development, uses and disposal towards sustainable innovation. Traditional toxicological assays are typically expensive, time-consuming and have low throughput; and they have been replaced by new approach methodologies (NAMs) focused on in vitro, in chemico and in silico approaches, along with alternative models. Caenorhabditis elegans has emerged as a complete model organism for predictive toxicology due to its transparent body, short reproductive and life cycles, and a fully sequenced genome with high homology with the human genome. In this review, we discuss the current status, state-of-the-art characterization techniques, and scientific gaps in nanotoxicity studies involving the carbon nanomaterials and the C. elegans model considering the last two decades of research. Moreover, we showed the existing supportive tools to evaluate the internalization and biodistribution of carbon nanomaterials in C. elegans and discussed their advantages and limitations. Methodological and experimental gaps must still be discussed with the scientific community; hence, we brought to light this discussion and point out future orientations and perspectives. This review will contribute for guiding the research with C. elegans, and harmonization of assays/protocols linked to computational tools and nanoinformatics approaches during the development of carbon nanomaterials.Key biological outcomes References Nanomaterial Features Exposure conditions Endpoints Strain Life stage Key biological outcomes References